Ileal Stenosis Occurred 3 Months after Blunt Abdominal Trauma - Kang, Gun-Hi; Jeon, Tae Joo; Seo, Dong Dae; Oh, Tae-Hoon; Kim, Soohyun; Cho, Hyun Sun; Bae, Byung Noe; Kim, Jung Yeon (The Korean journal of gastroenterology, 2011)
We present a case of ileal stenosis with delayed presentation 3 months after car accident. Ileal stenosis after blunt abdominal trauma is a rare clinical entity. We present CT and small bowel series 3 months after trauma. Image showed segmental thickening of intestinal wall and proximal bowel dilation. At surgery, a stenotic bowel loop was adjacent to a fibrotic mesentery. Histological examination showed ulcers, inflammatory cells and fibroblasts infiltrated to the muscularis mucosae, submucosa,and mesentery. The most likely cause, supported by most authors, implicates an injury to the mesentery. Post-traumatic ischemic bowel stenosis may result from even small tears and contusions of mesentery. Posttraumatic intestinal stenosis should be included in the differential diagnosis in a patient with a history of blunt abdominal trauma and signs of intestinal obstruction. KCI Citation Count: 1